Psychometrics of the Wrist Stability and Hand Mobility Subscales of the Fugl-Meyer Assessment in Moderately Impaired Stroke. Issue 1 (1st January 2015) - Page, Stephen J.; Hade, Erinn; Persch, Andrew
Abstract : Background: There remains a need for a quickly administered, stroke-specific, bedside measure of active wrist and finger movement for the expanding stroke population. The wrist stability and hand mobility scales of the upper extremity Fugl-Meyer Assessment (w/h UE FM) constitute a valid, reliable measure of paretic UE impairment in patients with active wrist and finger movement. Objective: The aim of this study was to determine performance on the w/h UE FM in a stable cohort of survivors of stroke with only palpable movement in their paretic wrist flexors. Design: A single-center cohort study was conducted. Method: Thirty-two individuals exhibiting stable, moderate upper extremity hemiparesis (15 male, 17 female; mean age=56.6 years, SD=10.1; mean time since stroke=4.6 years, SD=5.8) participated in the study, which was conducted at an outpatient rehabilitation clinic in the midwestern United States. The w/h UE FM and Action Research Arm Test (ARAT) were administered twice. Intraclass correlation coefficients (ICCs), Cronbach alpha, and ordinal alpha were computed to determine reliability, and Spearman rank correlation coefficients and Bland-Altman plots were computed to establish validity. Results: Intraclass correlation coefficients for the w/h UE FM and ARAT were .95 and .99, respectively. The w/h UE FM intrarater reliability and internal consistency were greater than .80, and concurrent validity was greater than .70. This also was the first stroke rehabilitative study to apply ordinal alpha to examine internal consistency values, revealing w/h UE FM levels greater than .85. Concurrent validity findings were corroborated by Bland-Altman plots. Conclusions: It appears that the w/h UE FM is a promising tool to measure distal upper extremity movement in patients with little active paretic wrist and finger movement. This finding widens the segment of patients on whom the w/h UE FM can be effectively used and addresses a gap, as commonly used measures necessitate active distal upper extremity movement.